Family‐based treatment: Where are we and where should we be going to improve recovery in child and adolescent eating disorders. Issue 4 (6th December 2018) - Lock, James; Le Grange, Daniel
Abstract: Objective: Family therapy has long been advocated as an effective intervention for eating disorders. A specific form of family therapy, one that utilizes family resources, has proven especially effective for adolescents with anorexia or bulimia nervosa (AN and BN). First developed in London, a behaviorally focused adaptation, called family‐based treatment (FBT), has been manualized and systematically studied in six randomized clinical trials for adolescent AN and two for adolescent BN. Method: This Commentary focuses on manualized FBT; what we know, what we do not know (yet), and what we hope for . Results: We do know that efficacy data for FBT, especially adolescent AN, are quite robust, even though remission rates remain elusive for more than half of all cases. While preliminary, moderators of FBT for adolescent AN have been identified and could aid us in determining the most (or least) responsive patient groups. And weight gain (∼2.5kg) by week four has been confirmed as an early predictor of remission at end‐of‐treatment. What we do not know, yet, is whether specific adaptations to manualized FBT will confer improved remission rates. Discussion: Finally, and in terms of what is hoped for, we highlight the promise of improved access, dissemination, and implementation of FBT.